2020
DOI: 10.22336/rjo.2020.4
|View full text |Cite
|
Sign up to set email alerts
|

Visual evoked potential in the early diagnosis of glaucoma. Literature review

Abstract: Visual evoked potentials (VEP) are a significant visual electrophysiological diagnostic exam, which can be used as a suitable objective measure of optic nerve function. The topic was greatly debated and many correlations between the magnitude of the VEP latency parameters and parameters of Humphrey static perimetry suggested that the abnormal cortex responses in patients with glaucomatous changes could be tested by both electrophysiological and physical methods. Moreover, the optic nerve glaucomatous damage ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In our study, we noted no significant change in OCT results after 6 months of treatment. As report in literature the damage to the optic nerve observed by the reduction of the ganglion cell layer and the thickness of retinal fiber revealed by OCT correlates with the VEP latency parameters ( 28 ). However, these anomalies are later and appear after the impairment of the visual field.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In our study, we noted no significant change in OCT results after 6 months of treatment. As report in literature the damage to the optic nerve observed by the reduction of the ganglion cell layer and the thickness of retinal fiber revealed by OCT correlates with the VEP latency parameters ( 28 ). However, these anomalies are later and appear after the impairment of the visual field.…”
Section: Discussionmentioning
confidence: 65%
“…Visual evoked potential is an important visual electrophysiological diagnostic exam, which can be used as an objective measure of optic nerve function. Correlations between the magnitude of VEP latency parameters and automated visual parameters have suggested that cortex responses in glaucoma patients could be tested by electrophysiological methods ( 28 ). Electrophysiology in glaucoma brings valued information, which detects macular ganglion cell dysfunction and VEP can be of aid in the evaluation of “glaucoma suspects” even before a detectable loss appears by visual field examination ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The degree of the retinal, optic nerve and visual impairment may be rapidly and objectively determined by visual electrophysiological testing. The cerebral cortex generates bioelectricity when the retina is activated and this is known as the VEP ( 27 ). The VEP has a decreased amplitude and a delayed peak when the optic nerve is damaged by ocular trauma ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the visual field assessments, they may of advantage as being completely objective, hence more unbiased examination of the function of the visual pathway. This objectiveness is because cognitive factors (like tiredness, stress and others) or patient"s motor skills (especially for the elder patients) are absent (35) .…”
Section: Visual Field Testingmentioning
confidence: 99%